2020
DOI: 10.1002/jms.4450
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix alterations in low‐grade lung adenocarcinoma compared with normal lung tissue by imaging mass spectrometry

Abstract: Lung adenocarcinoma (LUAD) is the second most common cancer, affecting both men and women. Fibrosis is a hallmark of LUAD occurring throughout progression with excess production of extracellular matrix (ECM) components that lead to metastatic cell processes. Understanding the ECM cues that drive LUAD progression has been limited due to a lack of tools that can access and report on ECM components within the complex tumor microenvironment. Here, we test whether low-grade LUAD can be distinguished from normal lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
(56 reference statements)
2
16
0
Order By: Relevance
“…[26]. These results accorded with previous reports on the functions of immune and stromal cells in the TME of LUAD patients [27][28][29].…”
Section: Kinase Targets Of Hub Genessupporting
confidence: 91%
“…[26]. These results accorded with previous reports on the functions of immune and stromal cells in the TME of LUAD patients [27][28][29].…”
Section: Kinase Targets Of Hub Genessupporting
confidence: 91%
“…In parallel, an image is created by combining the data of the spot location with the corresponding measured mass spectrum. In the field of cancer research, MALDI-MSI has been used to analyze drug (metabolite) distribution in the TME, tumor subtyping, tumor grading, or biomarker discovery [55,[76][77][78][79]81]. MALDI-MSI is also used to predict tumor progression and clinical outcomes [56,69].…”
Section: Matrix-assisted Laser Desorption Ionization Mass Spectrometr...mentioning
confidence: 99%
“…For example, elevated collagenase type III levels in the extracellular matrix discriminate low-grade adenocarcinoma (AD) (stage I-III) from adjacent healthy lung tissue. More in-depth analysis revealed that hydroxylated peptides display a specific spatial pattern within the TME, which allows for the differentiation of tumor subtypes [76]. Spatially guided proteomics and histology-guided spatial metabolomics of NSCLC allowed for the differentiation of two NSCLC subtypes: adenocarcinoma and squamous cell carcinoma (SCC).…”
Section: Tumor (Sub)classification and Tumor Gradingmentioning
confidence: 99%
“…Tissue was prepared as previously with minor modifications [34,35,43,44]. Previously stained tissues were incubated in xylene for 24-72 h to remove coverslips.…”
Section: Imaging Mass Spectrometry (Ims) Preparationmentioning
confidence: 99%